The effects of case study teaching on learners’ language literacy skills in physical sciences classrooms - Mogofe, Romulus Asaph; Athiemoolam, Logamurthie (Universitas Majalengka, 2025)
Studies indicate that low language literacy skills in the language of teaching and learning (LoLT) can be a barrier to Physical Sciences learning. In addition, South African learners’ language literacy skills in the LOLT are below the level that would allow effective science learning. This study employed a mixed methods design to investigate the effects of case study teaching on learners’ language literacy skills in Physical Sciences classrooms in schools in the low performing Sekhukhune District of Limpopo Province in South Africa. The sample comprised 122 Grade 10 learners from four schools (two rural and two urban) selected through a stratified sampling process. Quantitative data were collected through a reading comprehension (pre-/post-) test (with the content validity index (CVI) of 100 % (1) and the reliability index (Cronbach’s alpha value) of 0,74 when piloted within the study context) while qualitative data was gleaned using face-to-face interview. The quantitative data was analysed both inferentially (using t-test and Cohen’s d-value), and descriptively (means and percentages) which were computed through PSPP statistical package while the qualitative one was analysed thematically using coding methods. The results of this study indicate that the mean performance of 6,44 for the EG and 3,87 for the counterparts in the CG with the p-value of 0,00 measured at the 95% confidence level. From the results, it can be concluded that case study teaching improves the language literacy skills of Physical Sciences learners at secondary school level. The results further indicate that the effect size for rural group is similar to their urban counterparts, which implies CST has a potential to improve rural learners’ language literacy skills as much as that of their urban counterparts. The qualitative data revealed that case studies improved language literacy skills because of their real-life relevance and comprehension, engagement through surprise element, group discussion and argumentative skills, constructive arguments and language comprehension. The study recommends the use of CST in science classrooms to improve learners’ language literacy. The study also recommend further studies with larger samples, under different context and over a prolonged period of time as it was conducted with a small sample over a relatively short period of time.